PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI ERA DIGITAL - Hafizi, Rahmani; Suyoto, Suyoto; Rahmadi, Rahmadi; Aslamiah, Aslamiah; Cinantya, Celia (Jurnal Manajemen Pendidikan, 2025)
The transformation of education in the digital era demands rapid adaptation from teachers, both in pedagogical practices and professional performance. In this context, transformational leadership and organizational culture play a vital role in enhancing teacher performance. This article aims to analyze the relationship between transformational leadership and organizational culture in improving teacher performance within digital-based educational environments. Using a literature review approach, this study synthesizes findings from relevant research published over the past five years. The analysis reveals that transformational leadership contributes to fostering work motivation, individual development, and teachers’ readiness to embrace technological change. Concurrently, an inclusive and innovative organizational culture strengthens collaborative spirit and workplace stability. Furthermore, the study finds a synergistic relationship between transformational leadership and organizational culture that collectively supports improved teacher performance. These findings suggest that enhancing the quality of digital education requires an integrated strategy that aligns leadership practices with the development of an adaptive organizational culture. The study recommends systematic implementation of transformational leadership and reinforcement of adaptive organizational values in schools.